Patents and Competitive Awards of the Innovative Elderly Products Designed by Nursing Faculty and Students in Taiwan - Ku, Ya-Lie; Pan, Yi-Ting; Shia, Jo-Yun; Li, Yi-Lun; Hsu, Shu-Ting (International Journal of Innovative Research in Medical Science, 2018)
Because of the aged society in Taiwan, the principal investigator has conducted four innovative projects to develop the four elderly innovative products with four groups of leaders. This paper introduces four innovative elderly products designed by the nursing faculty and students in Taiwan, including modified enema device, combination of turning and positioning auxiliary devices, and urine catheter fixation device for the bedridden elders. Four innovative elderly products have obtained the patents as well as awarded in 2017 International Innovation and Invention Competition by the organizations of Chinese Innovation and Invention Society and Moscow International Invention Society. Following the four innovative elderly products, the investigator would plan to conduct the evidences-based testing of the effectiveness for these products to improve the quality of care for the bedridden elders in terms of preventing or solving their clinical problems such as bedsores, constipation, and comfort.